2018
DOI: 10.1026/0932-4089/a000278
|View full text |Cite
|
Sign up to set email alerts
|

Der Einfluss von Resilienz auf qualitative Formen der Arbeitszufriedenheit

Abstract: Zusammenfassung. Das Arbeitszufriedenheitsmodell von Bruggemann (1974) unterscheidet qualitative Arbeitszufriedenheitsformen (AZ-Formen), die sich auf das Befinden bei der Arbeit auswirken. Obwohl diese AZ-Formen auf individuellen Verarbeitungsprozessen basieren, wurden deren personenbezogene Einflussfaktoren bisher nur selten untersucht. Die vorliegende Arbeit überprüft diesbezüglich den Einfluss der individuellen Resilienz auf die AZ-Formen und untersucht deren Auswirkungen auf das Befinden bei der Arbeit. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 52 publications
0
7
0
1
Order By: Relevance
“…Thus, it seems that there are other factors that can explain the relationship between work engagement and pandemic-related stress. Indeed, studies have shown that personal resources such as high resilience can increase work engagement [ 70 ]. High levels of resilience may result from nurses’ awareness that their work is more important than ever in maintaining patient care during these times [ 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it seems that there are other factors that can explain the relationship between work engagement and pandemic-related stress. Indeed, studies have shown that personal resources such as high resilience can increase work engagement [ 70 ]. High levels of resilience may result from nurses’ awareness that their work is more important than ever in maintaining patient care during these times [ 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…This model is well known in German speaking countries (e.g. Inauen et al, 2015; Schlett et al, 2018) and represents a qualitative, dynamic approach to the concept of job satisfaction that is based on several, stress related cognitive processes differing between persons. Having a certain type of job satisfaction, therefore, should have an impact on how employees perceive stressors and cope with stress and strain at work.…”
Section: Introductionmentioning
confidence: 99%
“…In line with this view, the present study investigates five different types of job satisfaction as a specific form of rather stable personal resources relevant for employees’ self-regulation at work. Individuals belonging to these five types show significant differences in the level of personal resources such as self-efficacy, optimism, and mindfulness (Schlett et al, 2018). In short, we propose that these types of job satisfaction can function as an important moderator variable.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In der arbeits-und organisationspsychologischen Forschung werden als Vulnerabilitätsfaktoren für erlebte Belastungen die Persönlichkeitsdimension Neurotizismus oder emotionsbezogene Coping-Stile beschrieben (Langelaan, Bakker, van Doornen & Schaufeli, 2006;Lazarus & Folkman, 1984). Als individuelle Ressourcen gelten Selbstwirksamkeit, Optimismus oder Kontrollüberzeugungen (Schlett, Pauls & Soucek, 2018;Spector et al, 2002).…”
unclassified